Analisis Faktor-Faktor Yang Mempengaruhi Volume Pembelian Ikan Mas di Pasar Tradisional Kota Bogor Menggunakan Metode Regresi Linier Berganda - Indra Maulana; Fathan Dwinanda Putra; Muhammad Taufiqurrohman; Reva Putri Salsabila; Syabia Maharaina Suhada; Rasidin Karo Karo Sitepu; Thoifatul Munawwaroh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the factors influencing the volume of carp fish purchases in traditional markets in Bogor City. The research applies a quantitative approach using a survey method involving 50 respondents. The variables examined include the price of carp fish, consumer income, the price of substitute goods (tilapia), and the number of family members. Data were analyzed using multiple linear regression.The results show that the price of carp fish has a negative effect on purchase volume, while consumer income, the price of substitute goods, and the number of family members have positive effects. The coefficient of determination (R²) is 0.54, indicating that 54% of the variation in carp fish purchase volume can be explained by the model, while the remaining is influenced by other factors outside the study. The F-test results indicate that all independent variables simultaneously have a significant effect on the purchase volume of carp fish. Furthermore, elasticity analysis shows that the demand for carp fish is inelastic with respect to price, income, and substitute goods price, but elastic with respect to the number of family members.